Implementasi Metode Simple Additive Weighting (SAW) dalam Rekomendasi Laptop Ekonomis untuk Mahasiswa - Yolanda Victoria Damanik; Endang Kartika; Sabrina Fadillah; Muhammad Robbi Akbar Pohan; Victor Asido Elyakim P (Yayasan Literasi Sains Indonesia, 2024)
In today's digital era, laptops are a major necessity for students to support academic activities. However, budget limitations are often an obstacle in choosing a laptop that suits the needs and financial capabilities. This research aims to implement the Simple Additive Weighting (SAW) method in an economical laptop recommendation system for students. The way this method works is by calculating alternative choices based on predetermined weights and criteria then sorting to find the best alternative from all existing criteria. So that the results will get a laptop recommendation that is closest to the suitability of the needs of prospective laptop users. The criteria used in the study include price, processor, RAM, storage capacity, and battery life. Sample data is taken from 8 laptop models with a price range of 3-7 million available on the market. The results showed that the application of the SAW method successfully provided laptop recommendations that were in accordance with the needs and budget limitations of students. With this recommendation system, students can more easily choose a laptop that suits their academic needs and budget limitations. This research is expected to be a reference for the development of decision support systems in the selection of efficient and appropriate technology devices.